Framework: visual-spatial: a mediator effects on the autism spectrum disorders (ASD) achievement in speech utterance - Hassan, Muhamad Hafiz; Wardi, Rainal Hidayat; Abdullah, Mohamad Hariri; Isa, Badrul (Universiti Teknologi Mara, Kedah, 2022)
The abstract on Visual Image and Spatial Ability is the basis for consolidating the results of art therapy that can be utilized in terms of its design through art activities with therapeutic processes. Evidence-based learning related to the Emotional and Speech Utterance of a person and personality in developing design interventions that can support the therapeutic process. This study focuses on special (special needs) groups with Autism Spectrum Disorder (ASD). This is also contained in the eight types of multiple intelligences on the abilities and capabilities of a person born normally or abnormally. This has become an unavoidable necessity nowadays. Its effectiveness should be assessed by strategizing the therapeutic process of a patient from different backgrounds, whether in terms of genetic ability, race, family, place, culture, environment and religion. Each different lifestyle and experience make this therapeutic process necessary to unravel the complexity from becoming more serious. This study is in line with the need for rapid development of our country, not only sponsored by educated, technological, creative, skilled and cultured people but also have strong intelligence and personality as well as emotional stability. This paper aims to discuss visually supporting teaching strategies with the influence of the perceived approach (Picture Exchange Communication System PECS) on the development of speech utterance among children with Autism Spectrum Disorder (ASD). This is also to determine and analyse the effects of cognitive and affective factors in speech utterance using the visual-spatial approach.